Offline - Rashid, Imran; Kenner, Soren (Ascent Audio, 2019)
Authors Imran Rashid and Soren Kenner have sparked an international debate by revealing the "mind hacks" Facebook, Apple, Google, and Instagram use to get you and your children hooked on their products. In Offline, they deliver an eye-opening research-based journey into the world of tech giants, smartphones, social engineering, and subconscious manipulation. This provocative work shows you how digital devices change individuals and communities for better and worse. Offline is a must-listen if you or your kids use smartphones or tablets and spend time browsing social networks, playing online games, or even just browsing sites with news and entertainment. Learn how to recognize "mind hacks" and avoid the potentially disastrous side-effects of digital pollution. Unplug from the matrix. Learn digital habits that work for you.